Notch signaling and efficacy of PD-1/PD-L1 blockade in relapsed small cell lung cancer - Roper, Nitin; Velez, Moises J.; Chiappori, Alberto; Kim, Yoo Sun; Wei, Jun S.; Sindiri, Sivasish; Takahashi, Nobuyuki; Mulford, Deborah; Kumar, Suresh; Ylaya, Kris; Trindade, Christopher; Manukyan, Irena; et al. (Nature communications, 2021)
Immune checkpoint blockade (ICB) benefits only a small subset of patients with small cell lung cancer (SCLC), yet the mechanisms driving benefit are poorly understood. To identify predictors of clinical benefit to ICB, we performed immunogenomic profiling of tumor samples from patients with relapsed SCLC. Tumors of patients who derive clinical benefit from ICB exhibit cytotoxic T-cell infiltration, high expression of antigen processing and presentation machinery (APM) genes, and low neuroendocrine (NE) differentiation. However, elevated Notch signaling, which positively correlates with low NE differentiation, most significantly predicts clinical benefit to ICB. Activation of Notch signaling in a NE human SCLC cell line induces a low NE phenotype, marked by increased expression of APM genes, demonstrating a mechanistic link between Notch activation, low NE differentiation and increased intrinsic tumor immunity. Our findings suggest Notch signaling as a determinant of response to ICB in SCLC. Immune checkpoint blockade (ICB) benefits only a small subset of patients with small cell lung cancer (SCLC) and the mechanisms driving benefit are poorly understood. Here, the authors show that elevated Notch signaling predicts clinical benefit in ICB in relapsed SCLC.